2015
DOI: 10.2134/agronj15.0202
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Contribution of Ionic and Agronomic Components toward Salinity Tolerance in Safflower

Abstract: Saffl ower (Carthamus tinctorius L.) is a versatile crop species that is well adapted to arid and semiarid conditions. Limited information is available on the response of saffl ower genotypes to salinity stress under fi eld conditions. Th e objective of this study was to investigate the eff ects of fi eld salinity on seed yield, yield components, and leaf ionic concentrations in diff erent saffl ower genotypes. A 2-yr fi eld experiment was conducted in normal (E1) and saline (E2) fi eld conditions using 64 saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
2
18
1
Order By: Relevance
“…In contrast to safflower (Yeilaghi et al, 2015) and other longer duration sunflower experiments (Di Caterina, Giuliani, Rotunno, De Caro, & Flagella, 2007;Ceccoli et al, 2012;Shahbaz et al, 2011), we found no link between leaf Na and tolerance. A key difference in these other studies and our experiment is the duration of stress.…”
Section: (C)contrasting
confidence: 99%
“…In contrast to safflower (Yeilaghi et al, 2015) and other longer duration sunflower experiments (Di Caterina, Giuliani, Rotunno, De Caro, & Flagella, 2007;Ceccoli et al, 2012;Shahbaz et al, 2011), we found no link between leaf Na and tolerance. A key difference in these other studies and our experiment is the duration of stress.…”
Section: (C)contrasting
confidence: 99%
“…It is quantitatively inherited and a large number of QTLs associated with plant height have been reported in different crop systems (Wu et al, 2010 ; Morris et al, 2013 ; Zanke et al, 2014 ). In previous studies, safflower germplasm have revealed significant variations for plant height (Yeilaghi et al, 2015 ; Kumar et al, 2016 ). However, genetic loci influencing this trait have not yet been identified.…”
Section: Discussionmentioning
confidence: 98%
“…Safflower is also used for extraction of dyes, several medicinal applications and as a plant factory for production of pharmaceuticals (Dajue and Mündel, 1996 ; Flider, 2013 ; Carlsson et al, 2014 ; Zhou et al, 2014 ). Additionally, its ability to grow under low moisture and high salinity conditions would give it a competitive edge over other oilseed crops in arid zones (Kaya et al, 2011 ; Bahrami et al, 2014 ; Yeilaghi et al, 2015 ; Ebrahimi et al, 2016 ). Currently, safflower is cultivated in around 20 countries in a total area of 1,140,002 hectares and production of 948,516 tons (FAOSTAT) 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Traditional safflower oil, rich in polyunsaturated linoleic acid is valued for human health reasons as the high linoleic content leads to significant reductions in blood cholesterol levels [15,16] although not suitable for prolonged frying due to low oxidative stability at high temperatures. On the contrary, oil which is rich in monounsaturated oleic acid shows high oxidative stability, which makes it suitable for food purposes and an alternative to olive oil in arid and semi-arid regions in the world [2,11,22,23]. Moreover, oleic acid is characterized by a high single point of unsaturation and this represents an attractive characteristic to industry due to the large range of potential chemical products.…”
Section: Introductionmentioning
confidence: 99%